TorakochirurgiaComparison of the diagnostic value of positron emission tomography and computed tomography for mediastinal lymph node metastatic involvement in patients with non-small cell lung cancer - Bella, Mariusz; Dancewicz, Maciej; Świniarska, Joanna; Bławat, Przemysław; Kowalewski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Metastatic involvement of mediastinal lymph nodes in patients with non-small cell lung cancer (NSCLC) is routinely evaluated by computed tomography of the chest (CT). Short axis of a lymph node longer than 10 mm and its enhancement of at least 20 j.H. suggest metastatic involvement of the lymph node. A new diagnostic tool to evaluate mediastinal lymph nodes is positron emission tomography integrated with computed tomography (PET-CT), which enables the assessment of pathological glucose metabolism in lymph nodes. Aim: To compare the value of PET-CT and TK for prediction of mediastinal lymph node metastatic involvement in patients with NSCLC. Material and Methods: Thirty-two patients (26 males and 6 females) with NSCLC were retrospectively analyzed. To evaluate mediastinal lymph nodes all patients underwent CT and PET-CT. If metastatic involvement of the lymph nodes was suspected in any of the two imaging techniques, mediastinoscopy or videothoracoscopy was performed. In all cases pathological verification of lymph nodes was done. Sensitivity, specificity, accuracy and positive and negative predictive value were calculated for PET-CT and CT. Results: Metastatic involvement of mediastinal lymph nodes was suspected in CT in 11 patients, in PET-CT in 14 and simultaneously in both in nine cases. Sensitivity, specificity, accuracy and positive and negative predictive value for PET-CT were 91, 85, 87% and 78 and 94% respectively and 75, 90, 84, 81 and 85% respectively for CT. Therapeutic management initially planned on the basis of CT was changed after PET-CT in two patients (6.3%). Conclusions: PET-CT compared with CT had higher sensitivity and negative predictive value in evaluation of mediastinal lymph nodes in patients with NSCLC.